Improving Food Safety and Improving the Fundamentals of Reducing the Negative Effects on The Environment - Abdumuminova Rano Narbuvaevna; Bulyaev Zokir Karimovich; Mallaeva Mavjuda Mahramovna (Genius Journals, 2022)
In order to ensure that the quality and safety of agricultural products in the country meet international standards, the Cabinet of Ministers of 18.11.2020 adopted a separate regulation on the safety of organic products, raw materials and organic and mineral fertilizers. Therefore, it is now important to grow organic fresh fruits and vegetables. At the same time, ensuring food security in a healthy lifestyle today is in some sense dependent on the composition of fruits and vegetables.It is known that the amount of nitrate in fruits and vegetables exceeds the allowable level in exchange for overuse of mineral fertilizers to increase the productivity of agricultural products. For this reason, with the help of methods recommended by the Uzbek Research Institute of Horticulture, Viticulture and Enology, green manure (siderate) was used in a way that provides the right amount of nitrate in fruits and vegetables.According to the study, the amount of nitrate in the fruit fed with mineral fertilizers was 80.8 mg / kg (the norm is 60 mg / kg), and in the case of biological fertilizers, this figure was 50.9 mg / kg. As a result, along with the nitrate content of the fruit, the mineral and organic contamination of the currently depleted soil is prevented. In conclusion, the use of biological (siderate) fertilizers as an alternative to mineral fertilizers in the prevention of nitrate poisoning is generally acceptable.
Keywords: food safety; nitrates; organic products; acidity